(untitled) (Research, Society and Development, 2022)
Rolling rolls are used in forming sheets, bars, profiles, etc. Some cylinders, when cast, receive some type of heat treatment, then they are machined and inspected in which non-conformities or dimensional errors can be verified during the machining process. These defects are verified in the face of an audit report, which depending on can be recovered via welding and then reworked on a CNC lathe. After the SMAW welding and machining processes, the cylinder undergoes a rigorous inspection process to ensure quality control, as two important tribological processes can be added to the manufacturing process by duplicating or combining internal and surface defects. The comparative research procedures adopted were the metallographic laboratory practice of the generated chips, using the hardness test in the regions of the heat-affected zone ZTA and base metal MB. The results of the recovery procedures showed a combination of analysis of the SMAW welding process and analysis of the chips from turning machining of the recovered region. Differences were verified in the machined regions of the chips in terms of type and shape of chips, in addition to the morphological changes of the graphites. The chips presented in the HAZ region were presented as shear to brittle materials and in the base metal region as a shear material chip. Graphites have changed due to the cooling temperature of the welding process by the heat generated in machining, combined. The work proposal can lead to confirmation of the link between the welding and machining areas and its relationship with inspection quality control.